2003
DOI: 10.1039/b211134a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific solvation determined by intermolecular nuclear Overhauser effect—measurements and molecular dynamics

Abstract: Site-specific solvation has been determined by intermolecular NOE measurements between solvent and solute. The experimental effect is shown on the four compounds 2-butanol, L-alanyl-L-tryptophan (Ala-Trp), adenosine and the disodium salt of adenosine 5'-monophosphate (5'-AMP) in the two solvents water and dimethyl sulfoxide (DMSO). The strength of NOE transfer correlates with the average distribution of solvent molecules around the corresponding solvation sites represented by the number of solvent molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(11 reference statements)
2
15
0
Order By: Relevance
“…Larger‐than‐expected values of σ HFNOE for peptide–fluoroalcohol interactions have been observed previously and have been interpreted to indicate a solvent‐sorting process that increases the concentration of fluoroalcohol near the peptide surface relative to the nominal concentration of the bulk solution 32, 34, 35. This notion is consistent with molecular dynamics simulations of such systems 35, 36, 53–57. However, selective solvation or solvent sorting cannot be responsible for all of the enhanced values of σ HFNOE observed in the present work.…”
Section: Resultssupporting
confidence: 91%
“…Larger‐than‐expected values of σ HFNOE for peptide–fluoroalcohol interactions have been observed previously and have been interpreted to indicate a solvent‐sorting process that increases the concentration of fluoroalcohol near the peptide surface relative to the nominal concentration of the bulk solution 32, 34, 35. This notion is consistent with molecular dynamics simulations of such systems 35, 36, 53–57. However, selective solvation or solvent sorting cannot be responsible for all of the enhanced values of σ HFNOE observed in the present work.…”
Section: Resultssupporting
confidence: 91%
“…1. First, interaction of the water molecules with the two aromatic protons of the adenine ring is different, which is in agreement with our recently published results [11] from application of this methodology to conformational analysis of the anomeric centre in these two compounds; this different interaction is observed not only in the water solutions but also in the water-TFE mixtures. Second, the presence of the TFE as a cosolvent clearly affects the results of these measurements, and this effect depends on the pH of the sample.…”
Section: Intermolecular Homonuclear Noe Measurementssupporting
confidence: 89%
“…In our earlier work we reported several examples of this technique [8,9,10]. For the two molecules adenosine (1) and adenosine monophosphate disodium salt (2, (5′-AMP)) we have shown there is a distinct site-specific homonuclear NOE between water and the two aromatic protons [11], and we have interpreted these results in terms of easier steric access of water molecules towards H-2 in the drawn conformation of adenosine given in Scheme 1. In this work we want to demonstrate preferential solvation by TFE and show the conformational preference of adenosine in water-TFE mixtures.…”
Section: Introductionmentioning
confidence: 89%
“…It has been shown that the aromatic protons at 2 and 4-7 positions, which are involved in the 1 L b transition, exhibit the strongest intermolecular NOE (nuclear Overhauser effect) interactions of the side chain of Trp with DMSO. The result has been interpreted as a hydrophobic interaction between the methyl groups of DMSO and the protons of the indole group [33]. The significant alteration of the 1 L b band observed for NATA in DMSO shows that the solvent/solute interaction has a dipole-induced dipole and/or van der Waals character (Fig.…”
Section: The 1 L B Of Trp In Dmso Is a Results Of A Specific Solvent/smentioning
confidence: 97%
“…The sulfoxide oxygen of DMSO is capable of forming a hydrogen bond with the NH-group of the indole ring. On the other hand, DMSO shows a specific interaction with the Trp residue [33]. It has been shown that the aromatic protons at 2 and 4-7 positions, which are involved in the 1 L b transition, exhibit the strongest intermolecular NOE (nuclear Overhauser effect) interactions of the side chain of Trp with DMSO.…”
Section: The 1 L B Of Trp In Dmso Is a Results Of A Specific Solvent/smentioning
confidence: 99%